INVESTIGATING THE NUMBER SENSE ABILITY OF PRE-SERVICE MATHEMATICS TEACHERS - Nourma Pramestie Wulandari; Vivi Rachmatul Hidayati; Dwi Novitasari; Tabita Wahyu Triutami; Ulfa Lu’luilmaknun (MaPan : Jurnal Matematika dan Pembelajaran, 2020)
Abstract:This research aims to identify the components of number sense of pre-service mathematics teachers. Pre-service mathematics teachers need a good number sense ability as a provision to transfer knowledge to students. This research uses a quantitative method. Subjects in this research are 14 third year pre-service mathematics teachers. The instrument used was in the form of 30 items of number sense questions that were developed based on number sense components, that is, understanding and skills about numbers, using number and operations on numbers, and using number and operation skills in calculations. The results showed that number sense ability of pre-service mathematics teachers' was still at a moderate level, which is 76.67%. Pre-service mathematics teachers also lack numbers' comprehension and skills elements.Abstrak:Penelitian ini bertujuan untuk menyelidiki komponen number sense mahasiswa calon guru matematika. Calon guru matematika memerlukan kemampuan number sense sebagai bekal untuk mentransfer pengetahuan kepada siswa. Penelitian ini merupakan penelitian kuantitatif. Subjek penelitian adalah 14 calon guru matematika tahun ketiga. Instrumen yang digunakan berupa 30 item soal number sense yang dikembangkan berdasarkan komponen number sense, yaitu pemahaman dan keterampilan tentang bilangan dan penggunaan operasi bilangan, dan menerapkan keterampilan bilangan dan operasi dalam perhitungan. Hasil penelitian menunjukkan bahwa kemampuan number sense mahasiswa calon guru matematika masih berada pada level sedang yakni 76,67%. Mahasiswa calon guru matematika masih lemah dalam komponen pemahaman dan keterampilan tentang bilangan.